Private Sector Early Child Care and Education in Malaysia: Workforce Readiness for Further Education - Lydia Foong; Palanisamy K. Veloo; Mogana Dhamotharan; Carynne Loh (Kajian Malaysia, 2018)
Studies from several countries have shown that qualified educators in early childhood programmes make a significant difference in providing quality Early Child Care and Education (ECCE) have resulted in improved outcomes for young children. Given this fact, the Malaysian government has proposed to raise the minimum qualification of all preschool teachers to a diploma in early childhood education by 2020. This study examines the status of the private sector early childhood workforce in Malaysia and their readiness for further training. A stratified sample comprising 3,087 teachers was asked to complete a paper-andpencil questionnaire that explored their readiness for further education. Results of the study show that a large proportion of private sector teachers are young, under qualified, inexperienced and underpaid. Teachers are aware of the need to upgrade their skills and are ready to do so if given the opportunity. The study suggests that there is an urgent need to attend to private sector teacher professionalism so that quality early childhood care and education can be provided to the very young in the country by the private sector.